Comparitive Evaluation of Geometric Dynamic Channel Allocation Over Other Channel Allocation Schemes - Khader, Abdulla (1998)
Wireless services are one of the strongest growth areas in telecommunications today. Cellular voice is well established as a high-end service in most areas, but demand is increasing rapidly. In cellular systems, the geographical region is split using a regular topology, into cells each containing one base station. The base station should assign a channel that is not currently used within some specified distance. There are many kinds of channel assignment methods used in mobile communication starting with Fixed Channel Assignment (FCA), through Dynamic Channel Assignment (DCA) and Hybrid Channel Assignment (HCA). Personal Communication Services (PCS's) have been introduced as a mass-market phone service. The capacity, however, is now a critical issue for all of these services. The solution to the increasing spectrum efficiency demand in Personal Communication Services (PCS's) is the implementation of Dynamic Channel Allocation (DCA) strategy with distributed control. This thesis concentrates on one ,specific class of dynamic channel allocation called the Geometric Dynamic Channel Allocation (GDCA). The main feature of the GDCA lies in its ability to organise the dynamic resource assignment so that the resulting carrier usage pattern resembles what corresponds to other strategies , as long as that is compatible with the offered traffic pattern. Besides that, the overall performance advantage of GDCA over other strategies increases , as the offered traffic becomes larger.